2013
DOI: 10.1371/journal.pone.0068366
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β2-Microglobulin/Hemochromatosis Enhances Radiation Sensitivity by Induction of Iron Overload in Prostate Cancer Cells

Abstract: BackgroundBone metastasis is the most lethal form of several cancers. The β2-microglobulin (β2-M)/hemochromatosis (HFE) complex plays an important role in cancer development and bone metastasis. We demonstrated previously that overexpression of β2-M in prostate, breast, lung and renal cancer leads to increased bone metastasis in mouse models. Therefore, we hypothesized that β2-M is a rational target to treat prostate cancer bone metastasis.ResultsIn this study, we demonstrate the role of β2-M and its binding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The spread of metastasis may occur via the bloodstream or the lymphatic systems or through both routes [64]. Previous studies have shown that activated β2M is related with the cancer progression of human prostate [12,65], ovarian [17], colon cancer [66], lymphoma and leukemia [67]. β2M controls tumor metastasis and EMT to bone and other soft tissues [14].…”
Section: Discussionmentioning
confidence: 99%
“…The spread of metastasis may occur via the bloodstream or the lymphatic systems or through both routes [64]. Previous studies have shown that activated β2M is related with the cancer progression of human prostate [12,65], ovarian [17], colon cancer [66], lymphoma and leukemia [67]. β2M controls tumor metastasis and EMT to bone and other soft tissues [14].…”
Section: Discussionmentioning
confidence: 99%
“…β2-m protected against the influx and accumulation of intracellular iron, and lower levels of intracellular iron activated HIF-1α and its target genes including EMT markers and VEGF [31,36]. Knocking down either the HFE protein or β2-m resulted in mesenchymal to epithelial transition (MET), a reversal of EMT, decreased cell proliferation and increased apoptosis in PCa cells [42]. β2-m activates intracellular signaling axes mediated by ERK and sterol regulatory element-binding protein-1 (SREBP-1), that drive lipogenesis and lipid and lipid raft-mediated signaling and could potentially enhance the survival of cancer cells [34].…”
Section: Osteomimicry In the Pca Bone Metastatic Phenotype Activates mentioning
confidence: 99%
“…β2-m activates intracellular signaling axes mediated by ERK and sterol regulatory element-binding protein-1 (SREBP-1), that drive lipogenesis and lipid and lipid raft-mediated signaling and could potentially enhance the survival of cancer cells [34]. These results together with the demonstration that β2-m-mediated multiple downstream converging signaling pathways, including AR, lipid, iron and ROS [31,36,42,43], could exert powerful influences on the fate of PCa cells and their clinical behavior.…”
Section: Osteomimicry In the Pca Bone Metastatic Phenotype Activates mentioning
confidence: 99%
See 2 more Smart Citations